Algae and Clay Water Additives Differentially Impact Survival and Microbial Community Structure in Sablefish (Anoplopoma fimbria) Rearing Tanks - Pierce, Melissa L.; Lee, Jonathan S. F.; Dodd, Emily; Poretsky, Rachel S. (Frontiers in Marine Science, 2019)
Algae, or “greenwater,” is a traditional water additive used in finfish aquaculture, but is associated with high costs and potentially harmful bacterial growth. “Claywater,” a mix of clay and seawater, has been explored as a replacement for greenwater. In some fish species, however, claywater reduces survival rates, but the mechanisms are not understood. A link between water additive and microbial community composition may exist. In this study, the effects of different water additives on the microbial communities of larval sablefish were studied. Three treatments were evaluated: a traditional greenwater additive, a claywater additive, and a greenwater additive switched to claywater after one week. Microbial communities were characterized using 16S rRNA gene sequencing, and sablefish survival and growth were recorded. Tank seawater microbial communities were significantly influenced by water additive (treatment). Sablefish microbiomes were significantly, but weakly influenced by treatment, and there were time-specific differences within the claywater treatment. Sablefish from the treatment that was switched after one week maintained microbiomes that were more similar to the initial greenwater treatment. In general, sablefish were dominated by Vibrionaceae OTUs. Variability in the sablefish microbiomes between tanks from the same treatment was high, especially in the claywater treatment, which may have confounded treatment effects. Larvae in the claywater treatment had significantly lower survival rates compared to greenwater and greenwater-claywater treatments, but no treatment effect was observed on sablefish growth (length). Overall, results suggest that claywater does not negatively impact survival or the microbial community of sablefish when preceded by one week of greenwater.